2009
DOI: 10.1002/chem.200801892
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic Conjugate Addition of Aldehydes to Vinyl Sulfones and Vinyl Phosphonates as Challenging Michael Acceptors

Abstract: Chiral framework: Chiral amines with pyrrolidine frameworks catalyze the enantioselective conjugate addition of a wide range of aldehydes to various vinyl sulfones and vinyl phosphonates in high yields and with enantioselectivities up to >99 % ee (see scheme). The high versatility of the Michael adducts is exemplified by various functionalizations with conservation of the optical purity.Chiral amines with a pyrrolidine framework catalyze the enantioselective conjugate addition of a broad range of aldehydes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(61 citation statements)
references
References 197 publications
1
57
0
3
Order By: Relevance
“…70 The reaction of 3,3-dimethylisobutyraldehyde and vinyl sulfone was computed. Because the five lowest-energy minima for the enamine formed by the pyrrolidine catalyst and 3,3-dimethylbutyraldehyde are anti , only the transition structures for si- face (“bottom”, major) and re- face (“top”, minor) attack on the anti enamine were considered (Figure 27).…”
Section: Enamine/iminium Catalysismentioning
confidence: 99%
“…70 The reaction of 3,3-dimethylisobutyraldehyde and vinyl sulfone was computed. Because the five lowest-energy minima for the enamine formed by the pyrrolidine catalyst and 3,3-dimethylbutyraldehyde are anti , only the transition structures for si- face (“bottom”, major) and re- face (“top”, minor) attack on the anti enamine were considered (Figure 27).…”
Section: Enamine/iminium Catalysismentioning
confidence: 99%
“…Four examples of asymmetric, organocatalytic A C H T U N G T R E N N U N G Michael addition to activated vinylphosphonates can be found in the literature. [50][51][52][53] Three of them apply the Michael addition of unmodified aldehydes or ketones catalyzed by chiral secondary amines for the formation of the corresponding enamine in the catalytic cycle. [50][51][52] The fourth work deals with chiral base-catalyzed Michael addition of bketoA C H T U N G T R E N N U N G esters.…”
Section: Vinylphosphonates In Asymmetric Organocatalysismentioning
confidence: 99%
“…[50][51][52][53] Three of them apply the Michael addition of unmodified aldehydes or ketones catalyzed by chiral secondary amines for the formation of the corresponding enamine in the catalytic cycle. [50][51][52] The fourth work deals with chiral base-catalyzed Michael addition of bketoA C H T U N G T R E N N U N G esters. [53] In 2007 Alexakis et al reported that in the presence of 86 a various aldehydes 106 can be added to tetraethyl methylidenebisphosphonate 107 a in a highly asymmetric fashion leading to the formation of geminal bisphosphonates 108 (Scheme 29).…”
Section: Vinylphosphonates In Asymmetric Organocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Therefore, for several years, a huge effort has been devoted to the development of new Michael acceptors in order to achieve useful adducts through enamine catalysis. For example, alkylidenemalonates, [6] vinyl ketones, [7] maleimides, [8] vinyl sulfones, [9] chalcones, [10] benzoquinones, [11] vinyl phosphonates, [12] a-keto-a,b-unsaturated esters, [13] a-phosphonate-a,bunsaturated esters, [14] b-keto-a,b-unsaturated esters [15] and b-thioester-a,b-unsaturated esters [16] have been tested. Most of the 1,4-addition adducts have been further transformed to get useful building blocks of high molecular complexity.…”
Section: Introductionmentioning
confidence: 99%